The essence of the global food problem - Malakhova, L.V. (ХНУ ім. В. Н. Каразіна, 2012)
The article deals with the essence of the global food problem. The results of the study are as follows: the food problem is of international significance and its solution cannot be achieved by isolated efforts of individual countries; statistics on the number of starving people around the world is analyzed; the main causes, affecting the aggravation of food situation in the world in general and especially in developing countries are identified.
Статья посвящена рассмотрению сущности глобальной продовольственной проблемы. В результате исследования было выявлено, что продовольственная проблема имеет международное значение и её решение невозможно достичь изолированными усилиями отдельных стран; проанализированы статистические данные о количестве голодающих людей во всех регионах мира; выявлены основные причины, оказывающие влияние на обострение продовольственной ситуации в мире в целом, и особенно в развивающихся странах.
Keywords: developing countries; global food problem; the reasons of the food problem